Gambaran Kesadaran dan Intensi Remaja Kurus Tentang Latihan Fisik - Farah Diba; Zahtamal Zahtamal; Imelda Pardede (Fakultas Kedokteran Universitas Riau, 2020)
Underweight is a public health problem and the incidence rate is still increasing worldwide, including in Indonesia. This condition is more common in adolescents due to inadequate food intake and lack of nutritional knowledge. The other factor that determines nutritional status is physical exercise. The purpose of this study was to describe the awarenesss and intentions of underweight adolescents about physical exercise. This research was a quantitative descriptive study. It was conducted at SMA Negeri 5 and 3 in Pekanbaru. Ninety two underweight subjects were obtained by purposive sampling technique. Data collected using questionnaire and then analyzed by univariate analysis. The results of this study found that 63% underweight adolescent were female and they were experiencing mild to severe underweight. Most subjects have moderate awareness (77.2%) and good intention (64.13%) about physical exercise. It can be concluded that underweight adolescents have moderate awareness and good intention about physical exercise, despite they are being underweight.